Apakah ada Hubungan antara Pola Asuh Orang Tua dengan Karakter Pelajar Pancasila? - Sinthian Susan (Universitas Negeri Malang, 2021)
Abstract: Pancasila is the embodiment of Indonesian students as lifelong students who have global competence and behave following the values of Pancasila, with six main characteristics: faith, fear of God Almighty, and noble character, global diversity, cooperation, independence, critical reasoning, and creative. One of the emphases in schools is not just curriculum achievement but the formation of character based on Pancasila. Learning strategies and school programs are made to make it happen. Of course, schools need to collaborate with families. Parenting patterns are patterns of interaction between parents and children, namely how to have good attitudes or behavior to be used as role models for their children. Parenting patterns consist of permissive, authoritarian, authoritative, and democratic parenting. On this occasion, the researcher wants to know whether there is a relationship between parenting patterns and the character of Pancasila students in class IX students at SMP Negeri Malang? This study aimed to determine the relationship between parenting patterns and the character of Pancasila students in class IX students at SMP Negeri 13 Malang. The method used is correlation research. The results of this study are that there is a significant positive relationship between parenting patterns and the character of Pancasila students. Abstrak: Perwujudan pelajar Indonesia yang belajar sepanjang hayat, memiliki kemampuan global dan menunjukkan perilaku yang sesuai dengan nilai Pancasila disebut sebagai pelajar Pancasila. Salah satu penekanan di sekolah adalah tidak sekedar pencapaian kurikulum, tetapi terbentuknya karakter yang berdasarkan pada Pancasila. Strategi pembelajaran dan program sekolah dibuat untuk mewujudkan karakter pelajar Pancasila dan sekolah diminta untuk berkolaborasi dengan orang tua. Kondisi ini menuntut orang tua untuk memberikan pola asuh yang sesuai untuk memenuhi kebutuhan anak. Tujuan penelitian ini untuk mengetahui hubungan antara pola asuh orang tua dan karakter pelajar Pancasila siswa kelas IX di SMP Negeri 13 Malang. Metode penelitian yang digunakan adalah korelasi. Hasil penelitian menunjukkan terdapat hubungan signifikan positif antara pola asuh orang tua dengan karakter pelajar Pancasila.